2016
DOI: 10.1186/s12864-016-2643-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the multi-host pathogen Erysipelothrix rhusiopathiae reveals extensive recombination as well as the existence of three generalist clades with wide geographic distribution

Abstract: BackgroundKnowledge about how bacterial populations are structured is an important prerequisite for studying their ecology and evolutionary history and facilitates inquiry into host specificity, pathogenicity, geographic dispersal and molecular epidemiology. Erysipelothrix rhusiopathiae is an opportunistic pathogen that is currently reemerging in both the swine and poultry industries globally. This bacterium sporadically causes mortalities in captive marine mammals, and has recently been implicated in large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 79 publications
3
86
0
Order By: Relevance
“…The results of this study also showed no clear correlations between the geographic origins or years of isolation of the strains and the PFGE patterns. This may be because of chromosomal rearrangements resulting from a high level of core genome recombination among E. rhusiopathiae strains (16). It is also possible that the serovar 1a strains analyzed in this study are not phylogenetically related because of homoplasy in serotype (16).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The results of this study also showed no clear correlations between the geographic origins or years of isolation of the strains and the PFGE patterns. This may be because of chromosomal rearrangements resulting from a high level of core genome recombination among E. rhusiopathiae strains (16). It is also possible that the serovar 1a strains analyzed in this study are not phylogenetically related because of homoplasy in serotype (16).…”
Section: Discussionmentioning
confidence: 95%
“…In each analyzed strain, Ͼ95.6% of the Illumina reads (mostly Ͼ99%) were mapped to the reference genome, and the mapped regions covered Ͼ98.0% (mostly Ͼ99%) of the reference genome (Table S1). A recent study clarified the existence of three distinct clades (clades 1, 2, and 3) and an "intermediate" clade between clade 2 and the dominant clade 3 within the species E. rhusiopathiae (16). To examine the phylogenetic position of the Japanese strains, we constructed a phylogenetic tree by including the strains belonging to clades 2 and 3 and the two recently sequenced Chinese strains, SY1027 and GXBY-1, both of which were isolated from septicemic pigs (17,18).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations